Underground knowledge: estimating the impacts of soil information transfers through experimental auctions - Murphy, D.M.; Roobroeck, D.; Lee, D.R.; Thies, J. (Wiley, 2020)
Soil degradation, a serious environmental problem in many developing countries, often necessitates the use of fertilizers to improve crop yields. However, smallholders usually do not have sufficient information about their soil nutrient levels to make profit‐maximizing decisions about fertilizer usage. We conducted two‐round experimental auctions to determine whether providing information and fertilizer recommendations from inexpensive soil testing kits to farmers in western Kenya affected their behavior and ability to optimize their input choices. We auctioned organic and inorganic agricultural inputs, dividing farmers into information treatments, and analyzed the data using double and triple difference estimations. We find that providing soil information has significant effects on farmers' willingness to pay for inputs. We then use Monte Carlo simulations to show that there is potential for high net benefits to farmers from individualized soil tests. These results suggest that soil testing can be a cost‐effective method to increase food security in the region.